Study on Chemical Decontamination Process Based on Permanganic Acid-Oxalic Acid to Remove Oxide Layer Deposited in Primary System of Nuclear Power Plant - 김초롱; 김학수; Chorong Kim; Haksoo Kim (Journal of nuclear fuel cycle and waste technology (Online), 2019)
고리 1호기는 원전해체 계획에 따라 영구정지 이후 가능한 한 빠른 시일 내에 원자로냉각재계통의 화학제염을 수행할 계획으로, 계통제염 기술 확보를 위해 한수원에서는 2014년부터‘원전 해체설계를 위한 냉각재계통 및 기기제염 상용기술 개발’연구과제를 통해 화학제염기술을 개발하고 있다. 본 연구를 위해 Lab. 규모 계통제염 공정장치를 제작하였으며, 계통제염 대상의 주요재료인 STS304, 316, 410, Alloy600, SA508을 사용하여 화학제염 공정실험을 수행하였다. 화학제염 공정실험의 목적은 산화-환원공정의 최적시간, 최적제염제 및 공정횟수를 도출하기 위함이다. 화학제염 공정실험은 과망간산-옥살산 기반의 단위공정 및 연속공정 실험, 과망간산+질산-옥살산 기반의 연속공정 실험으로 나누어 수행하였다. 그 결과 단위공정실험을 통해 최적공정 시간인 산화공정 5시간, 환원공정 4시간을 도출하였으며, 연속공정실험을 통해 최적제 염제와 공정횟수를 도출하였다. 최적제염제는 산화제의 경우 200 mg·L-1 과망간산 + 200 mg·L-1 질산이고, 환원제는 2000 mg·L-1 옥살산이며, 공정횟수는 STS304와 SA508의 경우 2 cycle, Alloy600의 경우 3 cycle 이상 수행하는 것이 적절할 것 으로 평가되었다. In accordance with the decommissioning plan for the Kori Unit 1 NPP, the reactor coolant system will be chemically decontaminated as soon as possible after permanent shutdown. This study developed the chemical decontamination process though the development project of decontamination technology of reactor coolant system and dismantled equipment for NPP decommissioning, which has been carried out since 2014. In this study, Oxidation/reduction process was conducted using system decontamination process development equipment of lab scale and was divided into unit and continuous processes. The optimal process time was derived from the unit process, and decontamination agent and the number of process were derived through the continuous processes. Through the unit process, the oxidation process took 5 hours and the reduction process took 4 hours. As optimum decontamination agent, the oxidizing agent was 200 mg·L-1 Permanganic acid + 200 mg·L-1 Nitric acid and the reducing agent was 2000 mg·L-1 Oxalic acid. In the case of the number of processes, all oxide films were removed during the two-cycle chemical decontamination process of STS304 and SA508. In the case of Alloy600, all oxide films were removed when chemical decontamination was performed for three cycles or more.